Influence of Interval, Circuit and Combined Training on Selected Skill Related Physical Fitness Variables and Performance Variables among High School Football Players - Kumar, Dr. G. Syam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Soccer requires peak physical conditioning of its players to be played at the highest level. The only way to achieve this level of conditioning is training specifically for soccer and the amount of running done in a match. The benefits of this training vary from better performance on the pitch (soccer field) for longer amounts of time to a decreased chance of injury or cramping before, during and after a match. Also, the better conditioned a player is, the more likely he is to perform with the same amount of skill necessary when passing, dribbling and shooting at the end of the game as the beginning. Interval training is a type of physical training that involves bursts of high-intensity work interspersed with periods of low-intensity work. The high-intensity periods are typically at or close to near-maximum exertion, while the recovery periods may involve either complete rest or activity of lower intensity. Interval training provides benefits to any healthy person such as improving fitness, health, speed and stamina; it’s a very demanding type of activity and certainly not one you would want to fly into without adequate preparation.